Hadith #4740 - Sunan Abi Dawud - Abdullah bin 'Amr bin al-'Aas; Bashr bin Shghaf بشر بن شغاف; Ma'tmar bin Sulaiman-al-Taufayl معتمر بن سليمان - الطفيل; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Sulaiman bin Tarkhan al-Taymi سليمان بن طرخان التيمي (Sunan Abi Dawud)
People will come forth from Hell by Muhammad’s intercession, will enter paradise and be named Jahannamis.
Grade: Sahih